Quantification of hyaluronan in human fasciae: variations with function and anatomical site. Issue 4 (24th July 2018) - Fede, C.; Angelini, A.; Stern, R.; Macchi, V.; Porzionato, A.; Ruggieri, P.; De Caro, R.; Stecco, C.
Abstract: Recently, alterations in fascial gliding‐like movement have been invoked as critical in the etiology of myofascial pain. Various methods have been attempted for the relief of this major and debilitating clinical problem. Paramount have been attempts to restore correct gliding between fascial layers and the movement over bone, joint, and muscular structures. One of the key elements that underlies such fascial movement is hyaluronan. However, until now, the precise content of hyaluronan within fasciae has been unknown. This study quantifies for the first time the hyaluronan content of human fascial samples obtained from a variety of anatomic sites. Here, we demonstrate that the average amount varies according to anatomic site, and according to the different kinds of sliding properties of the particular fascia. For example, the fascia lata has 35 μg of hyaluronan per gram of tissue, similar to that of the rectus sheath (29 μg g −1 ). However, the types of fascia adherent to muscle contain far less hyaluronan: 6 μg g −1 in the fascia overlying the trapezius and deltoid muscles. In the fascia that surrounds joints, the hyaluronan increases to 90 μg g −1, such as in the retinacula of the ankle, where greater degrees of movement occur. Surprisingly, no significant differences were detected at any site as a function of age or sex ( P ‐value > 0.05, t ‐test) with the sole exception of the plantar fascia. This work can provide a better understanding of the role of hyaluronan in fascia. It will facilitate a better comprehension of the modulation of the hyaluronan‐rich layer that occurs in relation to the various conditions that affect fascia, and the diverse factors that underlie the attendant pathologies.